Agustín Cueva in the 1960´s: Dilemmas about Ecuadorian Culture and Identity - Andrés Tzeiman (Íconos, 2017)
The present work traces the first stage of the work of Agustín Cueva (1937-1992), an Ecuadorian sociologist who represents one of the most important figures in the legacy of social thought in the second half of the 20th century, not only in his own country but also in Latin America. His works of the 1960s are studied, especially those during the second half of the decade since there is the beginning of the itinerary of his prolific intellectual production and, at the same time, it is the least widespread and more delayed stage in the approach of his work. This paper reviews both his most relevant contributions about art and culture in Ecuador, a topic that has been excluded in the analysis of his 60’s works, and the theoretical influences that Cueva received during this period of his intellectual trajectory.